Risk of amputations associated with SGLT2 inhibitors compared to DPP‐4 inhibitors: A propensity‐matched cohort study. Issue 12 (5th August 2018) - Adimadhyam, Sruthi; Lee, Todd A.; Calip, Gregory S.; Smith Marsh, Daphne E.; Layden, Brian T.; Schumock, Glen T.
Abstract : Aim: To determine the risk of amputations associated with sodium‐glucose co‐transporter‐2 inhibitors (SGLT2i) relative to dipeptidyl peptidase‐4 inhibitors (DPP4i). Materials and Methods: We conducted an active comparator, new user cohort study using data from the Truven Health MarketScan (2009‐2015) databases. Patients aged ≥18 years newly initiating SGLT2i or DPP4i between April 1, 2013 and March 31, 2015 were included. Patients were matched 1:1 on high dimensional propensity scores and followed until the earliest of any amputation, treatment discontinuation, disenrollment or end of study period (December 31, 2015). Cox proportional hazards models were used to estimate hazard ratios (HR) and robust 95% confidence intervals (CI) for amputation risk. Results: There were 30 216 comparable patients in each arm after matching. Over a median follow‐up of 0.6 years, there were 60 amputations (SGLT2i: 36; DPP4i: 24), most at the level of partial foot (75%) and associated with diabetes‐related vascular disease (66.7%). The incidence of amputations was higher among SGLT2i patients (1.62 vs. 1.15 per 1000 person‐years) with a HR of 1.38 (CI: 0.83‐2.31). In subgroup analyses, risk differed by type of SGLT2i: canagliflozin, HR 1.15 (CI: 0.63‐2.09); dapagliflozin or empagliflozin, HR 2.25 (CI: 0.78‐6.47). Conclusion: All SGLT2i had an elevated, though not statistically significant, risk for amputations.